AD, Volume 21, n° 2 & 3, 1996 - Full Issue - Journal System (Africa Development, 1996)
Contents Préface Africa Confronted with the Ravages of Neo-liberalism Bernard Founou-Tchuigoila ........................ 5 Ghana Beyond Crisis and Adjustment Kwame Ninsin.................................. 25 Le Sénégal au-delà de l'ajustement structurel: pour une stratégie de développement fondée sur des forces populaires Amady Aly Dieng ............................. 43 La crise économique continue Martin Ezo'o Bizeme & Jean-Paul Komon ..................... 67 Autonomous Economic and Social Development in Democracy: An Appreciation of the Mauritian 'Miracle' Amedée Darga ................................ 79 Botswana Economy still an Enclave Guy Mhone ................................ 89 Démocratisation de l'ajustement ou socialisation du développement au Zaïre Kankvvenda Mbaya ............................ 101 Nigeria Beyond Structural Adjustment: Towards a National Popular Alternative Development Strategy Tunde Babawale, Akin Fadahunsi, Abubakar Momoh & Adebayo Olukoshi ........ 119 La crise de la société malienne: une alternative Magassa Hamidou ......................... 141 Le Burkina Faso au-delà de l'ajustement structurel Basile L. Guissou...............................159 Reflections on Social Change in Mozambique (State Cvil Society and Social Progress in Mozambique) Eugenio Macamo ...............................185 South Africa: The Popular Movement in the Flux and the Reconstruction and Development Programme (RDP) Hein Marais ..................................... 211 The Arab World: Re-compradorization Samir Amin ..................................... 235 Maghreb, from one Myth to Another Ali El Kenz ...............................245 The Socio-economic Crisis in Southern Africa (Botswana, Malawi, Zambia, Zimbabwe) Guy Mhone ........................... 267 Afrique de l'Ouest: les conditions de la relance de la coopération Bernard Founou-Tchuigoua .................... 279 Book Review Gallais Jean - Les tropiques, terres de risques et de violences, Armand Colin, 1994, 271p. Mouhamadou Abdou ................................ 301 Publications Received and Acquired ................... 305